Turning the Tide on Poverty: Perceptions of leaders and leadership in economically distressed communities. Issue 3 (26th May 2016) - Worthy, Sheri Lokken; Tyler-Mackey, Crystal; Dyk, Patricia Hyjer; Monroe, Pamela A.; Welborn, Rachel
Abstract: The Turning the Tide on Poverty project (Tide) was a civic engagement effort launched in 14 economically distressed southern rural communities in the US. The impetus of Tide was to foster community involvement in identifying and planning "place-based" solutions to poverty. Pre, immediate post, and follow-up data were collected, and qualitative analyses revealed key themes. The purpose of this article was to discuss the perceptions of the leadership theme, defined as the way community members view their local leaders. Findings indicate that positive perceptions of leadership helped communities engage more effectively in Tide. Discussions about who the decision-makers were, styles of leadership used, and whether residents and community leaders interacted in a positive manner are further explored in the context of the Community Capitals Framework.